2005
DOI: 10.1002/cne.20456
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical mapping and quantification of expression of a putative type 1 serotonin receptor in the crayfish nervous system

Abstract: Serotonin is an important neurotransmitter that is involved in modulation of sensory, motor, and higher functions in many species. In the crayfish, which has been developed as a model for nervous system function for over a century, serotonin modulates several identified circuits. Although the cellular and circuit effects of serotonin have been extensively studied, little is known about the receptors that mediate these signals. Physiological data indicate that identified crustacean cells and circuits are modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 91 publications
5
35
0
Order By: Relevance
“…For example, 5-HT has been shown to enhance the synaptic response of the LG command neuron for escape in dominants and inhibit it in subordinates (Yeh et al, 1996(Yeh et al, , 1997. These results indicated that a change in status creates a persistent change in distant parts of the nervous system by mechanisms that may include changes in the type or balance of 5-HT receptors expressed in target cells (Spitzer et al, 2005(Spitzer et al, , 2008.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, 5-HT has been shown to enhance the synaptic response of the LG command neuron for escape in dominants and inhibit it in subordinates (Yeh et al, 1996(Yeh et al, , 1997. These results indicated that a change in status creates a persistent change in distant parts of the nervous system by mechanisms that may include changes in the type or balance of 5-HT receptors expressed in target cells (Spitzer et al, 2005(Spitzer et al, , 2008.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, as in crayfish (Yeh et al, 1996;Cattaert et al, 2010), the status-dependent changes in Mauthner excitability have been linked to status-dependent changes in serotonergic modulation (Whitaker et al, 2011). Other proximate mechanisms may result from the kinds of status-related differences in the nervous system already observed in many animals, including transmitter or neuromodulator concentration (Gutzler et al, 2010), receptor populations (Spitzer et al, 2005;Burmeister et al, 2007), changes in neuronal size and shape (White et al, 2002), neurogenesis (Kozorovitskiy and Gould, 2004;Song et al, 2007), and gross brain morphology (Holmes et al, 2007;O'Donnell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocytochemical staining has shown this receptor on efferent axons of the fifth thoracic ganglion (Spitzer et al 2005) near the terminals of 5-HT neurons that innervate the Dep MNs (Fig. 2).…”
Section: Structure-function Relationships Between 5-ht Processes and mentioning
confidence: 98%
“…Two 5-HT receptors have been identified in crayfish nervous system, and one of those, 5-HT 1␣ , may be present in the initial segments of the Dep MNs and the LG command neuron (Spitzer et al 2005). Immunocytochemical staining has shown this receptor on efferent axons of the fifth thoracic ganglion (Spitzer et al 2005) near the terminals of 5-HT neurons that innervate the Dep MNs (Fig.…”
Section: Structure-function Relationships Between 5-ht Processes and mentioning
confidence: 99%